Our experience in diagnostics and treatment of coronary artery fistulae - M. P. Radchenko; А. А. Dovgalyuk; Yu. L. Kuzmenko; A. V. Maksimenko; N. М. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2017)
Coronary artery fistulae (CAF) – congenital coronary pathology with abnormal connection between the coronary arteries and heart chambers or vessels (superior vena cava, pulmonary artery or pulmonary veins). In rare cases can be acquired pathology. According to statistics CAF is present in 0.002% of world population and diagnosed in 0,2–0,6% of patients during routine cardiac catheterization. This article contains data analysis of 41 cases of endovascular interventions in patients with coronary artery fistulae.Purpose. To evaluate results of endovascular interventions in patients with coronary artery fistulae.Materials and methods. Patients with echocardiography evidence of coronary-pulmonary fistulae underwent endovascular catheterization with selective coronary angiography for verification of anatomical type and hemodynamic significance. Depending on received data indications for surgical or endovascular treatment has been determined. No thromboembolic complications, signs of ischemia and occluding device migration, no mortality after endovascular CAF closure.Conclusions. Endovascular catheterization of cardiac chambers with selective coronarography is the method of choice in CAF diagnosis.